The effect of livestock grazing on surface runoff and soil erosion from sloping pasture lands in the Ethiopian highlands - Mwendera, E.J.; Mohamed-Saleem, M.A.; Dibabe, A. (Commonwealth Scientific and Industrial Research Organisation, 1997)
Effects of livestock grazing on surface runoff and soil erosion at varying slopes were studied in pasture lands within Ginchi watershed, Ethiopia. The results showed that livestock grazing in the watershed followed distinct seasonal and spatial patterns. During the rainy season, grazing pressure was greatest on the upper slopes (>5% slope) while the pressure shifted to the lower slopes during part of the dry season. Seasonal grazing pressure in different parts of the watershed was further complicated by the fact that during the rainy season and immediately after the rains, grazing was limited to individually designated pasture lands while during most part of the dry season, the entire watershed became a common grazing resource for livestock of watershed residents as well as those farmers outside the watershed. It was observed that, on pastures above 4.2% slope, there is the risk of erosion rates exceeding the estimated soil loss tolerable limit under the current grazing pressures (heavy grazing), while slopes exceeding 5.8% are likely to suffer soil erosion under moderate grazing pressure at the current level of biomass productivity. Since livestock are mobile, farmers tend to take advantage of this attribute by seasonally moving the livestock to different parts of the watershed. This study has demonstrated the need for better understanding of the resource use patterns beyond the individual farmlands, most preferably at watershed level, so that on-site and off-site effects of seasonal concentration of livestock can be incorporated into developing feed production and management strategies for improving the system productivity and environmental protection.